The structural mechanics of cell division in Trypanosoma brucei. - Vaughan, S; Gull, K (2008)
Undoubtedly, there are fundamental processes driving the structural mechanics of cell division in eukaryotic organisms that have been conserved throughout evolution and are being revealed by studies on organisms such as yeast and mammalian cells. Precision of structural mechanics of cytokinesis is however probably no better illustrated than in the protozoa. A dramatic example of this is the protozoan parasite Trypanosoma brucei, a unicellular flagellated parasite that causes a devastating disease (African sleeping sickness) across Sub-Saharan Africa in both man and animals. As trypanosomes migrate between and within a mammalian host and the tsetse vector, there are periods of cell proliferation and cell differentiation involving at least five morphologically distinct cell types. Much of the existing cytoskeleton remains intact during these processes, necessitating a very precise temporal and spatial duplication and segregation of the many single-copy organelles. This structural precision is aiding progress in understanding these processes as we apply the excellent reverse genetics and post-genomic technologies available in this system. Here we outline our current understanding of some of the structural aspects of cell division in this fascinating organism.